2021
DOI: 10.1021/acs.jproteome.1c00463
|View full text |Cite
|
Sign up to set email alerts
|

The Human and Mouse Islet Peptidome: Effects of Obesity and Type 2 Diabetes, and Assessment of Intraislet Production of Glucagon-like Peptide-1

Abstract: To characterize the impact of metabolic disease on the peptidome of human and mouse pancreatic islets, LC-MS was used to analyze extracts of human and mouse islets, purified mouse alpha, beta, and delta cells, supernatants from mouse islet incubations, and plasma from patients with type 2 diabetes. Islets were obtained from healthy and type 2 diabetic human donors, and mice on chow or high fat diet. All major islet hormones were detected in lysed islets as well as numerous peptides from vesicular proteins incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
2
9
1
Order By: Relevance
“…α-cells synthesize proglucagon that is the precursor for glucagon and possibly GLP-1 under conditions of stress ( 61 , 62 , 63 , 64 , 65 , 66 ). Yet for rat islets, we found no evidence for significant levels of GLP-1, a finding consistent with prior reports using human, mouse, and pig islets ( 67 , 68 ). This was demonstrated by the immunoassay of rat islet CM using anti-GLP-1 antibodies that detect total GLP-1 measured as fully mature GLP-1[7–36]amide, partially mature GLP-1[7–37], the degradation product GLP-1[9–36]amide, and the precursors GLP-1[1–36]amide and GLP-1[1–37].…”
Section: Discussionsupporting
confidence: 92%
“…α-cells synthesize proglucagon that is the precursor for glucagon and possibly GLP-1 under conditions of stress ( 61 , 62 , 63 , 64 , 65 , 66 ). Yet for rat islets, we found no evidence for significant levels of GLP-1, a finding consistent with prior reports using human, mouse, and pig islets ( 67 , 68 ). This was demonstrated by the immunoassay of rat islet CM using anti-GLP-1 antibodies that detect total GLP-1 measured as fully mature GLP-1[7–36]amide, partially mature GLP-1[7–37], the degradation product GLP-1[9–36]amide, and the precursors GLP-1[1–36]amide and GLP-1[1–37].…”
Section: Discussionsupporting
confidence: 92%
“…The gut-derived GLP-1 binds to its receptor on local afferent vagal nerve terminals, which ultimately signals for satiety, delaying gastric emptying and suppression of hepatic glucose release (106, 107). However, this model may not translate well to human islets due to differences in islet architecture, and in light of the recent findings that glucagon is the dominant peptide hormone secreted from human alpha cells (46).…”
Section: Role Of Glp-1: Intra-islet or Intestinal?mentioning
confidence: 99%
“…If both glucagon and GLP-1 are produced in a proportion of alpha cells, and are both sorted to secretory granules, the question arises: are they sorted to distinct granule populations, and released under different glucose conditions? These questions may have been answered in a very recent islet granule peptidomics study showing that both human and mouse islets produce 300-1000 times more glucagon than active GLP-1 (46), indicating that the processing of proglucagon to active GLP-1 in alpha cells is very inefficient. Also in this study, analysis of secreted proglucagon-derived peptides showed that both glucagon and active GLP-1 were released in parallel in response to either low (1 mM), medium (6 mM) or high (16.7mM) glucose concentrations.…”
Section: Regulated Secretory Pathway Of the Pancreatic Alpha Cellmentioning
confidence: 99%
“…In a recent study of a large number of fresh human pancreatic specimens obtained at surgery, it was found that the levels of GLP‐1 7–36amide were below detection limits in most biopsies, and low but detectable in about a third. A study of humans islets using single‐cell expression analysis reached the same conclusion [18]. The interpretation of this would be that a limited and variable processing to GLP‐1 7–36amide may occur in the pancreas, but that the amount of GLP‐1 formed is nevertheless very small.…”
Section: Background and Discoverymentioning
confidence: 81%